Preliminary Study on the Effect of 4DCT-Ventilation-Weighted Dose on the Radiation Induced Pneumonia Probability (RIPP) - Han Bai; Wenhui Li; Yaoxiong Xia; Lan Li; Jingyan Gao; Xuhong Liu (SAGE Publishing, 2021)
Purpose: The purpose of the present study was to evaluate the feasibility of using 4-dimensional computed tomography (4DCT)-ventilation-weighted dose analysis to predict radiation-induced pneumonia probability (RIPP). Methods and Materials: The study population for this retrospective analysis included 16 patients with stage III lung cancer. Each patient's 4DCT images, including end-inhale and end-exhale sequences, were used for the deformable image registration, and the Hounsfield units (HU) density-change was used to calculate the ventilation. A previously established equation was used to convert the original dose (OD) D 0, i in the lungs in the original plan (OP) to the weighted-dose (WD) D w, i in the weighted plan (WP). The patients were divided into 2 groups, one with radiation-induced pneumonia (RIP), and one without. The Spearman correlation analysis was used to analyze the correlation of RIP with ΔV 20 (ΔV x = V w, x in the WP - V 0, x in the OP), ΔMLD (ΔMLD = mean lung dose (MLD) in the WP - MLD in the OP), and ΔV 5 . Results: The results showed that 5 of the 16 patients were suffering from acute RIP, 4 of which had higher ΔV 20 and ΔMLD values than the rest of the patients. The results of the Spearman correlation analysis for those 4 patients were as follows: RIP vs. ΔV 20 , r = 0.5123; RIP vs. ΔMLD, r = 0.5119; RIP vs. ΔV 5 , r = 0.1904. Conclusions: The 4DCT-ventilation-based weighted-dose analysis showed some correlation between RIPP and both ΔV 20 and ΔMLD, when comparing the weighted-dose and the conventional dose-volume histogram (DVH) analyses.